MODEL REGRESI SEBAGAI PENDUGA PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP PENDAPATAN PETANI TUMPANGSARI STUDI KASUS KESATUAN PEMANGKUANHUTAN BOJONEGORO - Akub J Abdurachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The success of taungya depends on several factors, i.e. site quality, social and economic condition of peasants. This report was made as the result of taungya survey in Bojonegoro Forest District, East Java. The influence of several factors were estimated by the multiple regression equation.The effect of site quality variable is significant, and the effects of technology and family man power variables are highly significant, but the levels of education, labor cost, and peasant location do not significantly influence peasants' income from taungya. The growth of basal trees area is influenced by technology and production facility cost variables in highly significant level. This occurence showed that applying